Product Line Diversification as a Growth Strategy in the E-Commerce Market: From a Startup to a Multi-Million Dollar Company - Kochnev, Vladimir (Scientific Journal of Bielsko-Biala School of Finance and Law, 2025)
With growth needs continuing to rise, more and more E-commerce businesses are becoming prone to adopt product line diversification as a strategic option to enhance their growth, expand their market reach and revenue generation. But how effective diversification is depends on to which extent the economy acts in such a way as to support it, and this is to be understood: it is a function of consumer demand, logistics efficiency, technological uptake and regulatory constraints. An econometric non-linear model is developed in this study to study the effect of product diversification to revenue growth with range in 5 major e-commerce market - USA, UK, Germany, India and China, from year 2019 to 2023. Macroeconomic indicators, marketing expenditure, GDP growth, and AI based approach are involved in this model as inputs to the model to predict the effect of decreasing diversification on the overall company growth. It finds that diversification is positively associated with revenue growth but its effectiveness is contingent on the logistic efficiency, digital transformation of an economy and its regulatory policies. Data from the study supplies businesses and policymakers with data driven insights on when and how diversification can lead to constant e commerce expansion in the marketplace.